Special issue the legacy of Stuart Scheingold - Sarat, Austin (Bingley, U.K. : Emerald, 2012)
This special issue of Studies in Law, Politics, and Society focuses on the discourse of judging and the "language of judging" within many diverse legal scenarios. The volume features chapters specifically on: the "language of rights" within the context of abortion and same-sex marriage cases; discourses within the European Court of Justice; the modern-day place of politics in the US Supreme Court; and discussions on the two-court crisis which lead to the US Constitutional Convention of 1849. The chapters question the complex and conflicting relationship between politics and the law, understanding judicial independence, and offer an analysis of how the literary narrative of law plays a significant part in the delivery of legal judgement.
Introduction : Stuart Scheingold, a personal reflection / Austin Sarat -- The myth of the myth of rights / George I. Lovell -- "A madman full of paranoid guile" : the myth of rights in the modern American mind / Jeffrey R. Dudas -- Novelty and the politics of rights / Helena Silverstein -- Political criminology, the plural state, and the politics of affect / Leonard Feldman -- Phantom racism and the myth of crime and punishment / Naomi Murakawa -- Putting politics in its place : reflections on political criminology, immigration and crime / William T. Lyons, Lisa L. Miller -- Imagining otherness : the political novel and animal rights / Claire E. Rasmussen -- Scheingold's failure : his finest book / Malcolm M. Feeley -- Rights, community, and democracy : a sociolegal critique of the neoconservative case against rights / Michael McCann, Stuart Scheingold.
Print version record
Keywords: Scheingold, Stuart A; Law -- General; Law -- Indigenous Peoples; Law & society; Legal system: general; Sociological jurisprudence; Civil rights